Can cardiovascular drugs support cancer treatment? The rationale for drug repurposing. Issue 4 (April 2019) - Regulska, Katarzyna; Regulski, Miłosz; Karolak, Bartosz; Murias, Marek; Stanisz, Beata
Graphical abstract: Highlights: Cardiology drugs have anticancer effect. The renin-angiotensin system contributes to carcinogenesis. Beta blockers attenuate cancer migration. Heparins inhibit cancer spread. Statins exert chemopreventive effect. Abstract : Research on the concept of biological overlap between cardiovascular and oncological diseases is gaining momentum. In fact, in both conditions, the malfunction of common regulatory mechanisms, such as the renin-angiotensin system (RAS), sympathetic nervous system (SNS), coagulation cascade, sodium-potassium ATP-ases, and mevalonate pathway, occurs. Thus, targeting these mechanisms with well-known cardiology drugs, including angiotensin-converting enzyme inhibitors (ACE-Is), angiotensin receptor blockers (ARBs), β-adrenergic receptor blockers, statins, cardiac glycosides (CGs), and low-molecular-weight heparins (LMWHs), could be a novel, promising adjuvant strategy in cancer management. Thus, here we discuss the idea of repurposing cardiology drugs in oncology based on available preclinical and clinical data.